1992
DOI: 10.1002/j.1460-2075.1992.tb05380.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a portable determinant of cell cycle function within the carboxyl-terminal domain of the yeast CDC34 (UBC3) ubiquitin conjugating (E2) enzyme.

Abstract: The ubiquitin conjugating (E2) enzyme encoded by CDC34 (UBC3) in Saccharomyces cerevisiae is required for the G1 to S transition of the cell cycle. CDC34 consists of a 170 residue amino‐terminal domain that is homologous to that found in other E2s, followed by a 125 residue carboxyl‐terminal domain that is specific to CDC34. We found that a truncation mutant of CDC34 which lacked the CDC34 carboxyl‐terminal domain could not support the essential function of CDC34 in the cell cycle in vivo. To explore further t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 30 publications
5
78
0
Order By: Relevance
“…Consistent with our previous observation (5), when Ub K48R was used in place of the wild type Ub, Cdc34-catalyzed polyubiquitin chain formation was almost completely inhibited ( Fig. 2A) (24,25) and that residues 171-209 constitute a minimal motif both necessary and sufficient for binding to the SCF components (26). These findings prompted us to examine the role of the C-terminal tail of human Cdc34 in mediating the Nedd8 stimulated and ROC1-CUL1-dependent Ub polymerization by deletion analysis.…”
Section: Conjugation Ofsupporting
confidence: 91%
“…Consistent with our previous observation (5), when Ub K48R was used in place of the wild type Ub, Cdc34-catalyzed polyubiquitin chain formation was almost completely inhibited ( Fig. 2A) (24,25) and that residues 171-209 constitute a minimal motif both necessary and sufficient for binding to the SCF components (26). These findings prompted us to examine the role of the C-terminal tail of human Cdc34 in mediating the Nedd8 stimulated and ROC1-CUL1-dependent Ub polymerization by deletion analysis.…”
Section: Conjugation Ofsupporting
confidence: 91%
“…In an elegant experiment the C-terminal (substrate binding) domain was fused to the catalytic domain of yeast UBC2/RAD6. Subsequently it was demonstrated that this hybrid molecule with ubiquitin conjugating activity resulting from the RAD6 portion and substrate recognition conferred by the CDC34 part is able to rescue cdc34 mutants [31,32]. No phenotype has yet been described for the deletion of the yeast UbcH2 homologue UBC8.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular functions of only a handful of these extensions are known [38][39][40][41] , and to date, the structural basis for protein-protein interactions mediated by these extensions remain elusive. One of the best understood extensions is in the E2 Ubc2p, which interacts with the E3, Ubr1p.…”
Section: Discussionmentioning
confidence: 99%